Innovative Approach: The Role Of Counseling Guidance Teachers Through Zoom Meetings In Improving Learning Guidance And Learning Supervision For Vocational School Students In Jember - Haryono, Nono (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2024)
students who are less controlled in their relationships so there is a need for guidance and supervision in learning by counseling teachers. The role of the counseling teacher using Zoom Meeting Media shows the importance of context in the association known to students and the process of coaching to supervision by the students themselves so that the concepts received by students are more meaningful. This research is in the form of causal quantitative (causality quantitative) with the research subject of class X students of SMK Plus Bustanul Ma'arif Gumukmas in the 2023/2024 academic year. The purpose of this study is to increase the role of counseling teachers with Zoom Meeting media in improving the guidance and supervision of grade X students' learning. The data in this study are quantitative data obtained from tests of student knowledge and understanding through questionnaire tests. The results of this study indicate: the influence of the role of the counseling teacher by using Zoom Meeting media on student learning coaching is 78.8%, the influence of the role of the counseling teacher by using Zoom Meeting media on student learning supervision is 70.6%, and the influence of the role of the counseling teacher in using Zoom Meeting media on student learning coaching and supervision together is 79.8%. This means that the application of the counseling teacher's role approach in coaching and supervising students has a significant effect.